2009
DOI: 10.1007/s12325-009-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitizers in nonalcoholic fatty liver disease and steatohepatitis: Current status

Abstract: Nonalcoholic fatty liver disease (NAFLD), first described in 1980, is now recognized as one of the most common causes of elevated liver enzymes and chronic liver disease in Western countries. The incidence of NAFLD in both adults and children is rising, in conjunction with the burgeoning epidemics of obesity and type 2 diabetes mellitus. NAFLD often coexists with other sequelae of the metabolic syndrome: central obesity, type 2 diabetes, hypertension, and hyperlipidemia. NAFLD encompasses a spectrum of patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 62 publications
1
51
0
1
Order By: Relevance
“…Lifestyle modifications resulting in weight loss through decreased caloric intake and moderate exercise is generally believed to be beneficial in patients with NASH, but is often difficult to maintain in the long term. 133 Given that insulin resistance plays a dominant role in the pathogenesis of NASH, many studies have examined the use of insulin sensitizers. Results with metformin (a biguanide) have been heterogeneous, most studies have been small and have flaws in the design, and its effect may be largely related to its ability to induce weight loss.…”
Section: Prevention and Management Of Haart Liver Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle modifications resulting in weight loss through decreased caloric intake and moderate exercise is generally believed to be beneficial in patients with NASH, but is often difficult to maintain in the long term. 133 Given that insulin resistance plays a dominant role in the pathogenesis of NASH, many studies have examined the use of insulin sensitizers. Results with metformin (a biguanide) have been heterogeneous, most studies have been small and have flaws in the design, and its effect may be largely related to its ability to induce weight loss.…”
Section: Prevention and Management Of Haart Liver Toxicitymentioning
confidence: 99%
“…[139][140][141][142] However, it is unclear whether a thiazolidinedione-associated increase in adiposity and weight gain would ultimately limit its benefits. 133 In addition, long-term toxicities of these agents include a potential for cardiovascular events and fracture risk. Therefore, we need more information regarding the efficacy and safety of these agents before recommendations for safe use can be made.…”
Section: Prevention and Management Of Haart Liver Toxicitymentioning
confidence: 99%
“…NAFLD develops progressively from simple steatosis to nonalcoholic steatohepatitis (NASH), fibrosis and cirrhosis (2,3). Previous studies have suggested a 'two-hit' theory for the pathogenesis of NAFLD, including insulin resistance, oxidative stress, lipid peroxidation and mitochondrial dysfunction (4,5), with insulin resistance considered the major factor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, up to 15-25% of people with NASH may progress to having cirrhosis over 10 to 20 yr (3,25,29) The current standard of care for NAFLD/NASH is limited to ameliorating components of the metabolic syndrome, primarily through weight loss and/or improving insulin sensitivity with lifestyle interventions or surgery (22,30). Improving insulin sensitivity by the use of thiazolidinediones is being investigated in a growing number of trials (4,36). However, this strategic approach appears to be inadequate as these agents display only modest and variable efficacy for NAFLD/NASH (27).…”
mentioning
confidence: 99%